Exploring ethical leadership of school principals and teachers at two secondary schools in Johannesburg East District: a case study - Nyabeni, Nomsa (My University, 2020)
This purpose of this study was to explore the conceptualisation and experiences of ethical leadership among school principals and teachers in two secondary schools located in Johannesburg East District in the province of Gauteng. This study was underpinned by the interpretive paradigm and guided by a qualitative methodology within a case study design. The two schools were purposively sampled because of convenience, with two principals and six teachers serving as research participants. This study utilised Shapiro and Stefkovich’s (2011) Multiple Ethical Paradigm and Khoza’s (2012) Attuned Leadership–African Humanism as theoretical frameworks. All trustworthiness considerations and ethical issues were observed before the data was generated through semi-structured interviews and documents reviews. The findings pointed to school principals and teachers having a good understanding of ethical leadership. However, the findings revealed that most ethical leadership challenges experienced by teachers emerged from parents, the school management team and learners in the researched schools, whilst the principals’ challenges originated from teachers and school board members. There were various recommendations suggested that could be applied by the Provincial Department of Education, the Independent Schools Association of Southern Africa and schools internally to reduce unethical conduct in the researched schools. Some of the recommendations were that school principals and teachers’ unethical behaviours can be reduced through professional development and reinforcement of educational legislation that underpin professional ethical behaviour. The findings also suggested that there was a consensus between teachers and school principals regarding ethical leadership as an effective approach in promoting a positive school culture and conduct in the researched schools. This study recommends the Department of Education and the Independent Schools Association of Southern Africa should provide workshops and training on ethical leadership, this will assist in reducing the unethical conduct of school principals and teachers within schools.
A research report submitted in partial fulfilment of the academic requirements for the degree of Master of Education to the Faculty of Humanities, School of Education at the University of the Witwatersrand, Johannesburg, 2020
Keywords: Educational leadership; Leadership; Leadership--Moral and ethical aspects